Hitler Youth : [compact disc, unabridged] : growing up in Hitler's shadow - Bartoletti, Susan Campbell (Random House/Listening Library, 2006)
The story of a generation of German young people who devoted all their energy to the Hitler Youth and the propaganda that brought Hitler his power, and the youths that resisted the Nazi movement. "I begin with the young. We older ones are used up. But my magnificent youngsters! Look at these men and boys! What material! With them, I can create a new world."-Adolf Hitler, Nuremberg,1933. By the time Hitler became Chancellor of Germany in 1933, 3.5 million children belonged to the Hitler Youth. It would become the largest youth group in history. Susan Campbell Bartoletti explores how Hitler gained the loyalty, trust, and passion of so many of. Germany's young people. Her research includes telling interviews with surviving Hitler Youth members.